Look, Ma, no hands! A preliminary study of educational interventions aimed at setting realistic expectations of semi-autonomous vehicle technology. (December 2020) - Amre, Shruti M.; Steelman, Kelly S.
Advanced driver-assist features are becoming fairly ubiquitous as more cars are equipped with features like autosteer and lane assist. While these features are primarily developed to promote driver safety, there are reports that drivers are not maintaining adequate supervisory control when the features are engaged. Vehicle technology branding, misinformation provided by dealership sales representatives, and even internet memes may be responsible for creating unrealistic expectations about the driver's role when driving a semi-autonomous vehicle. In this experiment, we presented participants with a description of a fictitious semi-autonomous vehicle based off the Tesla Model 3 and one of two educational pieces based upon either the SAE levels of automation or an excerpt from an owner manual. We present the findings and discuss the implications for the development of educational interventions aimed at calibrating driver expectations about semi-autonomous vehicle technology and the role of the driver when using advanced driver-assist features.